Love Elements In The “His Sunrise My Sunset” Novel By Jan Hurst (2016): Psychological Approach - Andry Abner Farlind; Robby Satria (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study looks at the elements of love as they are presented in Jan Hurst’s novel “His Sunrise, My Sunset.” This descriptive qualitative research follows the romance that Jan Hurst had with her husband, whom she had known since they were teenagers. After that, they were blessed with two children and eventually got married, but ultimately, death kept them apart. The researcher used library research techniques on books and journal articles that were pertinent to the theory and the primary data source, which is the novel, in order to obtain information for the study. In addition, the researcher employed descriptive qualitative methodologies to analyze the gathered data. Every piece of data that was collected was examined using Erich Fromm’s 1956 theory. According to Fromm’s idea, “The Art of Loving,” love is an active force that needs knowledge and practice to be maintained. According to Fromm, four elements need to be developed in order to sustain the love you wish to cultivate: care, responsibility, respect, and knowledge. Love is nothing more than an empty emotion that will eventually pass away without these four elements. The study’s findings clearly demonstrate that the foundation of the love shared by the primary characters, Jan Hurst and her husband Steve Hurst, is care, responsibility, respect, and knowledge. In the end, words, sentences, and paragraphs are used to narratively explain each of the study’s findings.